Does Cosmetic Rhinoplasty Affect Nose Function?. (18th September 2011) - Pousti, Seyed Behzad; Touisserkani, Sam; Jalessi, Maryam; Kamrava, Seyed Kamran; Sadigh, Nader; Heshmatzade Behzadi, Ashkan; Arvin, Arash
Abstract : Objective . To evaluate the changes in nasal dimensions of healthy Iranian volunteered for cosmetic rhinoplasty after surgery using acoustic rhinometry. Methods . Pre- and postoperative nasal dimension of 36 cases undergoing cosmetic rhinoplasty were compared using acoustic rhinometry (AR), and the measured variables were distance to first and second constriction (d1, d2), first and second minimal cross-sectional area (MCA1, 2), and volume. Results . Mean age (SD) of cases were 24.63 (4.4) years. Septoplasty was performed in 12 cases (33.3%). After surgery, bilateral d1 and both MCA2 decreased significantly, while significant increase was observed in MCA1 postoperatively using decongestant. Cases with septoplasty experienced more increase in MCA1 and less constriction in MCA2 postoperatively. In cases with rhinoplasty alone, they received benefit from double osteotomy in MCA1. In either group of rhinoplasty with and without septoplasty, placing a strut was beneficial for patients. Discussion . The cross-sectional area of the nose is a major factor in the determination of airflow. Cosmetic rhinoplasty may generate a mix effect on nose function. Performing osteotomy may better help patients to save nasal patency, septoplasty is beneficial even in mildly deviated septums, and placing a strut may be beneficial in most of the cases.